Fishery products market in Romania - Magdalena Rahoveanu, Turek; Gheorghe N., Iosif (Economics of Agriculture, 2010)
Integrated management policies of water resources seeks to improve the efficiency, sustainability and equity of water allocations, using a multi-disciplinary approach that recognizes cultural diversity and socioeconomic disparities inside and among societies. Integrated management policies of water resources will benefit from a sound use of economic and financial instruments that allow decision makers and water users to achieve those goals in a context of democratic decision making. Market liberalization of water resources means that nations and states introduce tradable property rights to water as a means to "increase the productivity of water use, improve operations and maintenance, stimulate private investment and economic growth, reduce water conflicts, rationalize ongoing and future irrigation development, and free up government resources for activities that have a public good content or positive externalities. This study used questionnaires distributed in SE Region in order to obtain information on fish farm activity, access to fish resources, to fishing areas, fish prices and finally on the economic results obtained. A sample of 10 farms was studied, their having an average income being used to diagnose production and marketing activities in the current stage. This study considered the activity of two representative fish farms in SE Development Region.